«АЛПАМЫС» ДӘСТАНЫНЫҢ ӨГИЗ ЖЫРАЎ ВАРИАНТЫНЫҢ ҮЙРЕНИЛИЎИНДЕ Н.ДӘЎҚАРАЕВТЫҢ ОРНЫ - Турдымуратова, А.Б. (FAN va JAMIYAT, 2022)
The article describes the scientific view of the works by N. Davkaraev in the study of the epic "Alpamys" version of Ogiz Zhyrau.